Development of mobile-based e-modules integrate learning model vak (visual, auditory, kinesthetic) to foster self-reliance of learning basic programming on the students of Vocational High School - Aguwin Ardi Pranata; Wahyu Sakti Gunawan Irianto; Utomo Pujianto (VOLT : Jurnal Ilmiah Pendidikan Teknik Elektro, 2018)
This research aims to develop mobile-based e-Module that serves as the supporting media on subjects with Basic Programming using VAK (Visual, Auditory, Kinesthetic) model learning. This research using model ADDIE (Analysis, Design, Develop, Implement, Evaluate). The results of the development of E-Module is declared valid, so worthy of use in the learning process. It is supported through results percentage of validation by an expert media amounted to 96%, the result of the validation by the percentage of material of 88%, the result of the percentage of test products amounted to 89%, the result of the percentage of trial usage of 88% and for learning independence grade and tastefully. This is supported through the research results of 80%.